Litterature Review: Faktor-Faktor Penyebab Terjadinya Anemia Defisiensi Besi Pada Ibu Hamil di Indonesia - Muhammad Muslim; Masita Fujiko; Fitriya Idrus (KOLONI, 2026)
A mother’s nutritional status before and during pregnancy plays an essential role in supporting fetal growth. Malnutrition during pregnancy can lead to anemia, which is a global public health issue with far-reaching consequences for individuals and socioeconomic development. This literature review aims to examine the factors contributing to iron-deficiency anemia in pregnant women in Indonesia based on research publications from the past five years. The research method employed involved a review of relevant articles from national and international journals published between 2020 and 2025, using narrative analysis to identify dominant risk factor patterns. The review results indicate that the primary risk factors include the mother’s age at risk, parity, adherence to iron tablet intake, gestational age, and the frequency of antenatal care visits. The conclusion confirms that sociodemographic factors (knowledge, education, income, age at marriage), obstetric factors (parity, inter-pregnancy interval), nutritional status (chronic energy deficiency), and health behaviors (adherence to iron tablet intake) have a significant association with hemoglobin levels and the prevalence of anemia in pregnant women.